Newly Recorded Freshwater Diatioms (Bacillariophyceae) From Two Wetlands of District Sirajganj, Bangladesh - Nahar, Khurshid; Khondker, Moniruzzaman (Journal of the Asiatic Society of Bangladesh, Science, 2018)
A total 9 diatoms taxa newly reported from the sediments of Joysagar and Sitlai Beel has been reported. These are Navicula cuspidata var. heribaudii Peragallo, N. grimmei Krabke, Navicula americana Ehr, Pinnulara major (Kutz.) Cleve, P. braunii (Grun.) Cleve. P. brevicosta Cleve, P. divergens, P. acrosphaeria Brebisson, P. stauroptera (Grun.) Cleve and P. hemiptera (Kutz.) Cleve. Asiat. Soc. Bangladesh, Sci. 44(1): 1-6, June 2018